COVID-19 Outbreak in North Italy: An Overview on Dentistry. A Questionnaire Survey - Cagetti, Maria Grazia; Cairoli, Jean Louis; Senna, Andrea; Campus, Guglielmo (International journal of environmental research and public health, 2020)
This survey assessed the symptoms/signs, protective measures, awareness, and perception levels regarding COVID-19 among dentists in Lombardy, Italy. Moreover, an analysis of the answers gathered in areas with different prevalence of the disease was carried out. All Lombardy’s dentists were sent an online ad hoc questionnaire. The questionnaire was divided into four domains: personal data, precautionary measures (before patient arrival; in the waiting room; in the operating room), awareness, and perception. Three thousand five hundred ninety-nine questionnaires were analyzed. Five hundred two (14.43%) participants had suffered one or more symptoms referable to COVID-19. Thirty-one subjects were positive to the virus SARS-CoV-2 and 16 subjects developed the disease. Only a small number of dentists (n = 72, 2.00%) were confident of avoiding infection; dentists working in low COVID-19 prevalence areas were more confident than those working in the Milan area and high prevalence area (61.24%, 61.23%, and 64.29%, p < 0.01 respectively). The level of awareness was statistically significantly higher (p < 0.01) in the Milan area (71.82%) than in the other areas. This survey demonstrated that dentists in the COVID-19 highest prevalence area, albeit reported to have more symptoms/signs than the rest of the sample, were the ones who adopted several precautionary measures less frequently and were the more confident of avoiding infection.